FESTIVAL SENI BERBASIS REALITA VIRTUAL: STUDI KASUS TATA KELOLA PENYELENGGARAAN SUMONAR 2020 - Oktala, Dwi; Barry, Syamsul; Hidayat, Dicky (Narada : Jurnal Desain dan Seni, 2024)
This study examines the governance of the Sumonar 2020 virtual art festival using a risk management approach. Organized by the Jogjakarta Video Mapping Project (JVMP), the festival focuses on video mapping and new media art, which has been offline since 2019. However, in 2020, the festival transitioned to a web-based virtual format in response to the Covid-19 pandemic. This study aims to analyze the success of Sumonar 2020 in utilizing virtual spaces as a form of risk mitigation for festival organization, as well as to identify the organizers' considerations and key factors contributing to its success, including technical strategies, creative innovations, and festival presentation. The research employs a qualitative approach to gain in-depth insights. Data collection was conducted through interviews and observations. The findings indicate that adopting a virtual format enables operational cost efficiency and reduces the risk of festival cancellation. The success of Sumonar 2020 reflects the organizers' ability to manage changes and highlights the importance of adaptability in festival management under various circumstances.